Fe1N4–O1 site with axial Fe–O coordination for highly selective CO2 reduction over a wide potential range. Issue 6 (6th May 2021) - Chen, Zhiqiang; Huang, Aijian; Yu, Ke; Cui, Tingting; Zhuang, Zewen; Liu, Shoujie; Li, Jianzhan; Tu, Renyong; Sun, Kaian; Tan, Xin; Zhang, Jiaqi; Liu, Di; et al.
Abstract : The proposed working mechanism of the electrochemical CO2 reduction reaction on Fe1 N4, Fe1 N4 –N1, and Fe1 N4 –O1 active sites. Abstract : On the path to deploying the electrochemical CO2 reduction reaction (CO2 RR) to CO, the narrow potential range under the high Faraday efficiency of CO (FECO ) still blocks its ultimate practical viability. Engineering the electronic structure via heteroatom doping is supposed to be efficient. However, a feasible synthesis and precise control are still challenging. Here, we propose a fast-pyrolyzing and controllable-activation strategy to construct an O-rich carbonaceous support and atomically dispersed FeN4 site with axial O coordination (Fe1 N4 –O1 ), which was confirmed by aberration-corrected electron microscopy and X-ray absorption spectroscopy. A wide potential range of 310 mV (−0.56 V to −0.87 V vs. RHE) could be achieved when FECO was continuously maintained at nearly 100%, which exceeded the existing results to the best of our knowledge. DFT calculations revealed that the superior performance originated from the axial O-coordination induced electronic localization enhancement, which could facilitate the desorption of CO and increase the energy barrier for the competitive hydrogen evolution reaction.